Does bilateral hearing aid fitting improve spatial hearing ability: a systematic review and meta-analysis. - Kumar, Sathish; Nayak, Srikanth; Kanagokar, Vibha; Pitchai Muthu, Arivudai Nambi (Disability & Rehabilitation: Assistive Technology, 2024)
Objectives: The ability to localize sound sources is crucial for everyday listening, as it contributes to spatial awareness and the detection of warning signs. Individuals with hearing impairment have poorer localization abilities, which further deteriorate when they are fitted with a hearing aid. Although numerous studies have addressed this phenomenon, there is a lack of systematic evidence. The aim of the current systematic review is to address the following research question, "Do behavioural measures of spatial hearing ability improve with bilateral hearing aid fitting compared to the unaided hearing condition?" Design: A comprehensive search was conducted by two independent authors utilizing electronic databases, using various electronic databases, covering the period of 1965 to 2022. The inclusion and exclusion criteria were formulated using the Population, Intervention, Compression, Outcome, and Study design (PICOS) format, and the certainty of evidence was determined using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) guidelines. Results: The comprehensive search resulted in 2199 studies, 17 studies for qualitative synthesis and 15 studies for quantitative synthesis. The collected data was divided into two groups, namely vertical and horizontal localization. The results of the quantitative analysis indicate that the localization performance was significantly better in the unaided condition for both vertical and horizontal planes. The certainty of our evidence was judged to be moderate, meaning that "we are moderately confident in the effect estimate. The true effect is likely to be close to the estimate of the effect, but there is a possibility that it is substantially different". Conclusion: The review findings demonstrate that the bilateral fitting of the hearing aid did not effectively preserve spatial cues, which resulted in poorer localization performance irrespective of the plane of assessment. Review Registration: Prospective Register of Systematic Reviews (PROSPERO); CRD42022358164 IMPLICATIONS FOR REHABILITATION: Hearing aids are a widely used rehabilitative method to compensate for the loss of audibility in individuals with hearing impairment. The current review highlights that, even though hearing aids can enhance audibility, they often fail to preserve spatial cues. This review paper provides a comprehensive summary of the existing literature, focusing on the preservation of spatial cues by hearing aids and the technologies that can enhance localization performance to a certain degree. The findings of the current study encourage both researchers and hearing aid manufacturers to advance their research methods pertaining to the preservation of spatial cues. This advancement has the potential to improve spatial awareness and possibly improve speech perception in the presence of noise in hearing aid users.